Implementation Of Augmented Reality As A Media To Improve DSLR Camera Knowledge - Arif Tri Novian; Agung Kharisma Hidayah; Yovi Apridiansyah; Dandi Sunardi (Jurnal Komputer, Informasi dan Teknologi, 2023)
The Augmented Reality Implementation application is an application or computer software designed in general to make it easier to learn about Multimedia material at SMK N 03 Padang Jaya school. AR has the advantage of being interactive and real time so that AR is widely implemented in various fields. The purpose of this study is to provide information on augmented reality technology to increase DSLR camera knowledge so that students can find out and make it easier for students to learn the shape of a DSLR camera, namely telephoto, camera body, lighting, and tripod. This application was created using the Blender application for making 3D models, and the Vuforia engine for making Maker, and Unity is the final step for building 3D models and Maker into an Android-based application. The results of this research can be seen that applying Augmented Reality technology can make it easier to study DSLR cameras so as to provide detailed information as expected based on the menu being tested.